2018
DOI: 10.1002/slct.201800145
|View full text |Cite
|
Sign up to set email alerts
|

Monodentate Coordination of N, N′‐Disubstituted Thiocarbamide Ligands: Syntheses, Structural Analyses, In Vitro Cytotoxicity and DNA Damage Studies of Cu(I) Complexes

Abstract: Structural analysis of three novel substituted thiocarbamide ligands N‐(naphthyl)‐N′‐(isobutoxycarbonyl) thiocarbamide (H2L1), N‐(4‐methoxyphenyl)‐N′‐(isobutoxycarbonyl) thiocarbamide (H2L2) & N‐(2‐methoxy‐4‐nitrophenyl)‐N′‐(isobutoxycarbonyl) thiocarbamide (H2L3) and their copper(I) complexes [(H2L1)2CuCl] (1), [(H2L2)2CuCl] (2) and [(H2L3)2CuCl] (3) was performed using various spectroscopic techniques (FT−IR, 1H and 13C NMR, UV‐Visible),TG analysis and single crystal X‐ray studies of (H2L1) and [(H2L1)2CuCl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The ability of the drugs to induce either apoptosis or necrosis seems to be a primary factor in determining their anti‐cancer efficacy . The cytotoxicity of the three complexes and their ligands were determined in terms of a colorimetric microculture assay (MTT) in HeLa and KB cells, yielding IC 50 values shown in Table , which also shows the comparison of experimental conditions with the results of cisplatin experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of the drugs to induce either apoptosis or necrosis seems to be a primary factor in determining their anti‐cancer efficacy . The cytotoxicity of the three complexes and their ligands were determined in terms of a colorimetric microculture assay (MTT) in HeLa and KB cells, yielding IC 50 values shown in Table , which also shows the comparison of experimental conditions with the results of cisplatin experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the important pharmacological activities ascribed to ureides are anti‐infectives, antitumor, anticancer and the various metabolic disorders include diabetes and hyperlipidemia . In a recent report by Pratap et al ., N,N′‐disubstituted thiourea molecules and their copper complexes showed moderate to potent cytotoxic properties against cervical carcinoma (2008 and C 13 ) and ovarian carcinoma (A2780, A2780/CP and IGROV‐1) cell lines. Moreover, the activities of the complexes were found to be stronger than the individual ligands and the latter have close cytotoxic properties compared to the present synthesized molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro cytotoxic results of copper(I) complexes of N-aryl, N'-isobutoxy/methoxycarbonyl thiocarbamide (C 106 -C 108 ) (Fig. 24) against A2780, A2780/CP, IGROV-1, 2008 (cervical), and C13* (cervical) cancer cell lines showed the higher anticancer potency than that of their coordinating ligands through the mechanism of DNA damage (Singh et al, 2015, Pandey et al, 2018. The copper complexes tend to break the strand of induced DNA via highly reactive hydroxyl radical (•OH) and superoxide anion (O 2 -) (Mosmann, 1983, Lopes et al, 1997, Lee & Steinert, 2003, Stepanenko & Dmitrenko, 2015.…”
Section: Copper(i) Complexes Of N N'-disubstituted Thioamidesmentioning
confidence: 99%
“…The presence of highly electronegative atoms or group of atoms on organic moiety has been found to cleave DNA more effectively (Shao et al, 2014, Stepanenko & Dmitrenko, 2015 so the complexes C 105 and C 106 showed significant anticancer effect toward IGROV-1, 2008 (cervical) and C13* (cervical) cell lines. (Singh et al, 2015, Pandey et al, 2018 A unique copper(I/II) complex of hydroxyl naphthalene derivative…”
Section: Copper(i) Complexes Of N N'-disubstituted Thioamidesmentioning
confidence: 99%
See 1 more Smart Citation